Camptothecin and camptothecin producing plants : botany, chemistry, anticancer activity and biotechnology /: botany, chemistry, anticancer activity and biotechnology. (2020) - Pullaiah, T; Raghavendra, P. B; Karuppusamy, S; Raveendran, V; Anuradha, M
No abstract available